Public relations roles empirically verified among public relations practitioners in Africa - Gené van Heerden; Ronél Rensburg (Communicare)
There is a lack of knowledge and understanding of the practice of public relations (PR) in Africa, which prohibits the continent to fulfil its responsibility towards the global PR society as well as other developing countries. Based on the findings of a master’s dissertation on the practice of PR in Africa, this article focuses on one of the concepts that were measured, namely PR roles. The article discusses current literature in the field of roles research and describes the empirical verification of two PR roles in Africa. Although the three roles of the PR strategist, manager and technician were measured, only two roles emerged during the factor analysis: the role of the strategist (Factor 1), and the combined roles of the technician/manager (Factor 2). The data was collected by means of a self-administered electronic questionnaire. Data analysis consisted of both Exploratory Factor Analysis (EFA) and Common Factor Analysis (CFA) where the underlying dimensions were extracted, indicating the items used to define the PR roles.